Peningkatan Hasil Belajar Siswa pada Pembelajaran Tematik Terpadu Menggunakan Model Tutor Sebaya di Sekolah Dasar - Yuza, Ramadhan Putra; Reinita, Reinita (Universitas Negeri Makassar, 2022)
This study aims to describe the improvement of student learning outcomes in integrated thematic learning using the Peer Tutor model in class IV SD Negeri 01 Pandam Gadang. The approach used is qualitative and quantitative approaches. The type of research is classroom action research (PTK). The research subjects were teacher and students in class IV. In RPP, it was seen that there was an increase from the first cycle whose average achievement was 81,94 % increasing to 94,44 % in very good category (SB). Next, in the learning process, it was seen that there was an increase in teacher activity from the first cycle whose average achievement was 85,71 % increasing to 92,85 % in the very good category (SB) in cycle II. Also seen an increase in student activity from the first cycle whose average achievement was 80,35 % increasing to 92,85 % in the very good category (SB) in cycle II. Student learning outcomes from the first cycle whose average achievement was 75,28 increasing to 87,05 in the good category (B) in cycle II. Thus, it can be conclude that the Peer Tutor model can improve student learning outcomes in integrated thematic learning in elementary school.